PEMBUATAN SMOOTHIES MANGGA SEBAGAI IMUN BOOSTER BAGI WARGA KOTA KULON KABUPATEN GARUT - Retty Handayani; Dila Aulia Dhasefa; Mia Wulan Sari; Monica Syafira Sukmawan; Neng Rofiah (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
The need for vitamins for body immunity, especially vitamin C, has increased since the Covid-19 pandemic. The scarcity of availability of this vitamin causes the price of vitamins to increase several times the usual price. Smoothies are drinks that contain yogurt or milk that are nutritious for increasing body immunity. The purpose of this activity is to increase public knowledge about the benefits of smoothies for immunity during the Covid-19 pandemic and provide solutions as a substitute for vitamins which are more expensive. This activity was carried out with PKK women in one of the houses of the Head of the RW Kelurahan Kulon Kota, Garut Regency. The method is by demonstrating how to make smoothies from mangoes accompanied by education and questions and answers regarding the content of mangoes which contain vitamins to increase body immunity. Mango smoothies were chosen because besides containing vitamin C which is nutritious for boosting the immune system, they also have a good taste because they contain milk or yogurt which contains protein which is good for the immune system. The results of this activity can add information and increase participants' knowledge from 17.3% to 98.6%.